Morphological structure of head and comparison between agraulos longicephalus hicks, 1872 and a. ceticephalus barrande, 1846, from the drumian of spain and czech republic (2020)
Order Ptychopariida has always been a problematic group concerning the taxonomic classification of Cambrian trilobites, and even though the temporality of this group is well known, the relation between this order with others, and, the difficulty for classifying ptychopariids have let to diverse problems in the phylogenetic classification of this, and other primitive orders of trilobites. Agraulos is one of the genera belonging to this order and is a common group of the middle Cambrian, it is a well-known genus inside ptychopariids, therefore, morphological knowledge about this taxon could be helpful to analyze morphological patterns among other species from the genus and even other genera inside the family Agraulidae, and even more, about the superfamily Ellipsocephaloidea. This paper provides a morphological statistical comparison based on landmark geometric morphometric techniques performed on specimens of two species of this genus, Agraulos longicephalus Hicks, 1872, and Agraulos ceticephalus Barrande, 1846, from the Drumian stage of Spain and the Czech Republic, respectively. The findings of this study suggest that, even though these species are morphologically similar, there are significant differences as to facial suture and glabella shape and size. In general, allometry in the samples seems to be an irrelevant factor related to morphological variation, but, individually, it is a significant source of variation in morphological patterns of A. ceticephalus. The results obtained from this study may contribute to future similar studies interested in analyzing the morphology of other species, genders, or even families inside order Ptychopariida.